A polyelectrolyte carbon-based hydrogel and a preparation method and application thereof
Patent Information
- Application Number
- CN202411419245.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-10-11
AI Technical Summary
纳米碳分散粒子与聚合物水凝胶复合结构的碳基水凝胶,如CN118047973A中涉及到的碳基水凝胶,其采用冷冻铸造方式构筑了多级有序孔结构,但是由于其孔尺寸较大,水输运过程的毛细作用较小,因此水输运速率较低
[0017](1)本发明通过加入聚电解质调控定向冷冻铸造过程中冰的成核大小,相比于传统冷冻铸造调控孔形貌的方式具有孔型可调的优势,可实现小尺寸取向孔的可控构筑,是一种普适的定向冷冻铸造碳基水凝胶的制备方法;
Smart Images

Figure CN119307058B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanomaterial preparation, specifically relating to a polyelectrolyte carbon-based hydrogel, its preparation method, and its application. Background Technology
[0002] Solar-powered water evaporation systems are low-cost and highly energy-efficient, playing a significant role in alleviating the energy crisis, reducing water pollution, and promoting seawater desalination. Based on the type of photothermal materials, they can be classified into: metallic materials, semiconductor materials, carbon-based materials, and polymer materials. Carbon-based photothermal materials possess broad spectral absorption characteristics, and the water evaporation energy of photothermal hydrogels is adjustable; therefore, carbon-based photothermal hydrogels have become a key material for the development of solar-powered seawater desalination technology.
[0003] In the research of hydrogel photothermal materials, a key focus needs to be on the impact of their water transport properties on photothermal evaporation. Efficient water transport channels not only provide a sufficient water supply for rapid evaporation but also enable the controllable construction of salt-resistant surfaces, facilitating the development of highly salt-resistant solar-powered seawater desalination structures. Currently, carbon-based photothermal hydrogel materials have developed composite structures of nano-carbon dispersed particles and polymer hydrogels, as well as photothermal hydrogels composed of continuous nano-carbon networks and polymers. Both types of carbon-based hydrogel structures possess abundant pore structures. The carbon-based hydrogel with nano-carbon dispersed particles and polymer hydrogel composite structures, such as the carbon-based hydrogel involved in CN118047973A, employs a freeze-casting method to construct a multi-level ordered pore structure. However, due to its large pore size, the capillary effect in the water transport process is weak, resulting in a low water transport rate. Photothermal hydrogels with polymer-composite continuous nano-carbon networks, such as the carbon nanotube hydrogels described in CN1 12934129A, employ a combination of hierarchical porous CNT aerogels and polymer hydrogels to obtain carbon-based hydrogels with a dual-network structure. However, these hydrogels exhibit a disordered, hierarchically distributed pore structure, resulting in low water transport efficiency. Therefore, there is an urgent need to develop controllable preparation methods for nano-carbon-based hydrogels with tunable pore structures to achieve efficient solar-powered seawater desalination in high-salt environments. Summary of the Invention
[0004] The main objective of this invention is to provide a polyelectrolyte carbon-based hydrogel, its preparation method, and its application, in order to overcome the shortcomings of the prior art.
[0005] To achieve the above-mentioned objectives, the technical solution of the present invention includes:
[0006] One aspect of the present invention provides a polyelectrolyte carbon-based hydrogel having an ordered oriented three-dimensional porous network structure formed by cross-linking of a water-soluble gel, a polyelectrolyte, and nano-carbon.
[0007] Furthermore, the orientation pore size of the polyelectrolyte carbon-based hydrogel is 1–20 μm.
[0008] Another aspect of the present invention provides a method for preparing a polyelectrolyte carbon-based hydrogel, comprising:
[0009] The water-soluble gel, water, and nano-carbon material are mixed evenly to obtain the first mixed solution;
[0010] The polyelectrolyte is mixed evenly with the first mixed solution to obtain a second mixed solution, and the pH value is adjusted.
[0011] The second mixed solution and crosslinking agent are mixed, and then frozen-cast in a directional manner to obtain a frozen nanocomposite gel.
[0012] The frozen nano-carbon composite gel was freeze-dried to obtain a polyelectrolyte carbon-based aerogel, which was then soaked in water to obtain a polyelectrolyte carbon-based hydrogel.
[0013] Another aspect of the present invention provides a polyelectrolyte carbon-based hydrogel prepared by the aforementioned preparation method.
[0014] Another aspect of the present invention provides a polyelectrolyte carbon-based dry gel prepared by drying the aforementioned polyelectrolyte carbon-based hydrogel.
[0015] Another aspect of the present invention provides the application of the aforementioned polyelectrolyte carbon-based hydrogel or polyelectrolyte carbon-based dry gel in the field of photothermal evaporation purification.
[0016] Compared with the prior art, the present invention has at least the following beneficial effects:
[0017] (1) This invention regulates the nucleation size of ice during directional cryogenic casting by adding polyelectrolytes. Compared with the traditional method of controlling the pore morphology in cryogenic casting, it has the advantage of adjustable pore shape and can realize the controllable construction of small-sized oriented pores. It is a universal method for preparing directional cryogenic carbon-based hydrogels.
[0018] (2) The polyelectrolyte carbon-based hydrogel prepared by the present invention has strong photothermal conversion ability and rich pore structure inside, which can be effectively applied to high-efficiency solar seawater desalination in high-salt environment. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments recorded in this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1This is a SEM image of a polyelectrolyte carbon-based hydrogel exhibited by efficient photothermal evaporation in a high-salt environment, according to a typical embodiment of the present invention.
[0021] Figure 2 This is a physical image of a polyelectrolyte carbon-based hydrogel exhibited by efficient photothermal evaporation in a high-salt environment, according to a typical embodiment of the present invention.
[0022] Figure 3 This is an infrared thermogram of a polyelectrolyte carbon-based hydrogel stable under a sunlight intensity in a typical embodiment of the present invention.
[0023] Figure 4 This is an infrared thermogram of a polyelectrolyte carbon-based dry gel stable under sunlight intensity in a typical embodiment of the present invention. Detailed Implementation
[0024] Given the difficulty in adjusting and controlling the pore structure of carbon-based photothermal hydrogel materials in existing technologies, the inventors of this invention, through long-term research and extensive practice, have proposed the technical solution of this invention. The main method involves using polyelectrolytes to regulate the nucleation size of ice during directional cryogenic casting, thereby preparing carbon-based hydrogels with controllable pore structures. The following will further explain the technical solution, its implementation process, and principles, but this should not be construed as limiting the scope of protection of this invention. Any non-essential improvements and adjustments made to this invention by those skilled in the art based on the above description are still within the scope of protection of this invention.
[0025] Polyelectrolytes are polymers with polar functional groups that exhibit strong interactions with water molecules. During cryogenic casting, they can regulate the ice growth structure, thereby influencing the morphology of the cryogenic pores. This invention develops a method for preparing polyelectrolyte-based carbon hydrogels by controlling the nucleation size of ice during directional cryogenic casting using polyelectrolytes. Compared to traditional cryogenic casting methods for controlling pore morphology, this strategy offers the advantage of adjustable pore shape, enabling the controllable construction of small-sized oriented pores. It is a universal method for preparing directional cryogenic carbon-based hydrogels and can be applied to solar-powered seawater desalination technologies in high-salt environments.
[0026] As one aspect of the technical solution of the present invention, a polyelectrolyte carbon-based hydrogel is provided, wherein the polyelectrolyte carbon-based hydrogel has an ordered oriented three-dimensional porous network structure formed by cross-linking of water-soluble gel, polyelectrolyte and nano-carbon.
[0027] Furthermore, the orientation pore size of the polyelectrolyte carbon-based hydrogel is 1–20 μm.
[0028] Furthermore, the orientation pore size of the polyelectrolyte carbon-based hydrogel is 1–10 μm.
[0029] Furthermore, the porosity of the polyelectrolyte carbon-based hydrogel is 80-90%.
[0030] Furthermore, the polyelectrolyte carbon-based hydrogel at 1kWm -2 At the given light power density, the water evaporation rate is 1.8–4.3 kg / m³. -2 h -1 .
[0031] As another aspect of the technical solution of the present invention, a method for preparing a polyelectrolyte carbon-based hydrogel includes: mixing water-soluble gel, water, and nano-carbon material evenly to obtain a first mixed solution;
[0032] The polyelectrolyte is mixed evenly with the first mixed solution to obtain a second mixed solution, and the pH value is adjusted.
[0033] The second mixed solution and the crosslinking agent were mixed and then directionally frozen to obtain a frozen nanocomposite gel.
[0034] The frozen nano-carbon composite gel was freeze-dried to obtain a polyelectrolyte carbon-based aerogel, which was then soaked in water to obtain a polyelectrolyte carbon-based hydrogel.
[0035] In some embodiments, the preparation method specifically includes: mixing the water-soluble gel with water to obtain a polymer solution, adding nano-carbon materials, and obtaining the first mixed solution.
[0036] In some preferred embodiments, the mass concentration of the water-soluble gel in the polymer solution is 10–50 mg / mL.
[0037] In some preferred embodiments, the mass concentration of the nano-carbon material in the first mixed solution is 0.1N2 mg / mL.
[0038] In some preferred embodiments, the water-soluble gel may include at least one of chitosan, sodium alginate, polyvinyl alcohol, polyethylene glycol, etc., but is not limited thereto.
[0039] In some preferred embodiments, the nano-carbon material may include at least one of graphene, carbon nanotubes, graphyne, fullerene, nano-carbon black, activated carbon, graphite powder, etc., but is not limited thereto.
[0040] In some embodiments, the preparation method specifically includes: stirring and mixing the polyelectrolyte with a first mixed solution to obtain a second mixed solution, adjusting the pH value to 1-2, stirring evenly, and then performing vacuum degassing treatment.
[0041] In some preferred embodiments, the polyelectrolyte may include at least one of polyanionic electrolytes, polycationic electrolytes, polyzwitterionic electrolytes, etc., but is not limited thereto.
[0042] In some preferred embodiments, the polyanionic electrolyte may include at least one of polyacrylic acid, polyacrylamide, polymethacrylic acid, polystyrene sulfonic acid, polyvinylphosphoric acid, etc., but is not limited thereto.
[0043] In some preferred embodiments, the polycationic electrolyte may include at least one of polyethyleneimine, polyethyleneamine, etc., but is not limited thereto.
[0044] In some preferred embodiments, the amphoteric polyelectrolyte may include at least one of natural nucleic acids, proteins, polydimethyldiallylammonium chloride-acrylamide-acrylic acid (P(DMDAAC-AM-AA)), etc., but is not limited thereto.
[0045] In some preferred embodiments, the mass concentration of the polyelectrolyte in the second mixed solution is 10N 50 mg / mL.
[0046] In some preferred embodiments, the acid used to adjust the pH includes, but is not limited to, at least one of hydrochloric acid, sulfuric acid, phosphoric acid, etc.
[0047] In some preferred embodiments, the concentration of the acid is 0.1 to 1 mol / L.
[0048] In some preferred embodiments, the vacuum degassing treatment time is 20-60 min, the vacuum degree of the vacuum degassing treatment is 1-20 Pa, and the temperature of the vacuum degassing treatment is 15-30 °C.
[0049] In some embodiments, the preparation method specifically includes: adding the crosslinking agent dropwise to a second mixed solution, pouring it into a cryogenic casting mold, and obtaining a cryogenic nano-carbon composite gel by directional cryogenic casting.
[0050] In some preferred embodiments, the mass ratio of the crosslinking agent to the second mixed solution is 1:100 to 1:200.
[0051] In some preferred embodiments, the crosslinking agent includes glutaraldehyde.
[0052] In some preferred embodiments, the temperature of the directional cryogenic casting is -20 to -196°C.
[0053] In some preferred embodiments, the directional cryogenic casting includes unidirectional or bidirectional cryogenic casting.
[0054] In some preferred embodiments, the working environment for the directional cryogenic casting is a cryogenic constant-temperature reaction bath or liquid nitrogen.
[0055] In some preferred embodiments, the raw material for the cryogenic casting mold may include at least one of stainless steel, copper, aluminum, silicone, polytetrafluoroethylene, nylon, plexiglass, etc., but is not limited to these.
[0056] This invention places nano-carbon hydrogel in a cryogenic casting mold, and then freezes the cryogenic casting mold in a low-temperature constant-temperature reaction bath or liquid nitrogen in one or two directions. Compared with traditional freezing methods, it can achieve ultra-fast freezing and controllable orientation pores, and can reduce phase separation, thereby obtaining a more uniform gel network.
[0057] In some embodiments, the preparation method specifically includes: thawing the frozen nano-carbon composite gel at room temperature, then freeze-drying it to obtain a polyelectrolyte carbon-based aerogel, and then soaking it in water to obtain a polyelectrolyte carbon-based hydrogel.
[0058] In some preferred embodiments, the settling time is 1 to 3 hours.
[0059] In some preferred embodiments, the freeze-drying time is 24 to 72 hours, and the freeze-drying temperature is 10 to 30°C.
[0060] In some preferred embodiments, the vacuum degree of the freeze-drying is 1N10 Pa.
[0061] In some preferred embodiments, the soaking time is 1 to 10 hours.
[0062] In some more specific embodiments, the preparation method specifically includes:
[0063] The water-soluble gel is mixed with water to obtain a polymer solution with a water-soluble gel mass concentration of 10-50 mg / mL, and nano-carbon material is added to obtain a first mixed solution with a nano-carbon material mass concentration of 0.1-2 mg / mL.
[0064] The polyelectrolyte is stirred and mixed evenly with the first mixed solution to obtain a second mixed solution with a polyelectrolyte mass concentration of 10-50 mg / mL. The pH value is adjusted to 1N2, and after stirring evenly, it is vacuum degassed in an environment of 1-20 Pa and 15-30 °C for 20-60 min.
[0065] The crosslinking agent was added dropwise to the second mixed solution at a mass ratio of 1:100 to 1:200, poured into a cryogenic casting mold, and cryogenically cast at -20 to -196°C to obtain a cryogenic nano-carbon composite gel.
[0066] The frozen nano-carbon composite gel was thawed at room temperature and allowed to stand for 1-3 hours. After being frozen in a refrigerator, it was freeze-dried in an environment with a vacuum of 1-10 Pa and a temperature of 10-30°C for 24-72 hours to obtain a polyelectrolyte carbon-based aerogel. After being soaked in water for 1-10 hours, a polyelectrolyte carbon-based hydrogel was obtained.
[0067] As another aspect of the technical solution of the present invention, a polyelectrolyte carbon-based hydrogel prepared by the aforementioned preparation method is provided.
[0068] As another aspect of the technical solution of the present invention, a polyelectrolyte carbon-based dry gel prepared by drying the aforementioned polyelectrolyte carbon-based hydrogel is also provided.
[0069] The polyelectrolyte carbon-based hydrogel prepared by this invention uses the electrostatic interaction between polyelectrolyte and water molecules to control the nucleation size of cryogenic ice crystals, which enables the controllable preparation of polyelectrolyte carbon-based hydrogels with smaller pores. The orientation pore size of the polyelectrolyte carbon-based hydrogel can be adjusted in the range of 1 to 20 μm.
[0070] Furthermore, the polyelectrolyte carbon-based hydrogel prepared in this invention incorporates molecular chains with different hydration functional groups through polymer network structure design, enabling the polymer chains and water molecules to form a richer hydration network via hydrogen bonding. Additionally, the polyelectrolyte carbon-based hydrogel prepared in this invention exhibits significant photothermal properties; its oriented porous structure facilitates controllable interfacial water transport, thereby achieving efficient interfacial photothermal water evaporation. Inside the polyelectrolyte carbon-based hydrogel, nano-carbon is loaded onto nanotube chains with the assistance of polymeric water chains, resulting in three-dimensional carbon nanotubes with a larger specific surface area, thus creating abundant interfacial water within the hydrogel.
[0071] As another aspect of the technical solution of the present invention, the application of the aforementioned polyelectrolyte carbon-based hydrogel or polyelectrolyte carbon-based dry gel in the field of photothermal evaporation purification is also provided.
[0072] Furthermore, the applications include, but are not limited to, applications in seawater desalination, wastewater treatment, or heavy metal salt treatment.
[0073] In summary, the polyelectrolyte carbon-based hydrogel prepared by this invention possesses strong photothermal conversion capabilities, a rich porous structure that forms abundant interfacial water, and a three-dimensional interpenetrating double network structure formed by non-covalent cross-linking of the polymer gel network and nano-carbon. These properties enable the polyelectrolyte carbon-based hydrogel to exhibit excellent environmental stability in high-salt environments, and it has broad application prospects in seawater desalination, wastewater treatment, and heavy metal salt treatment.
[0074] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be further described in detail below with reference to the accompanying drawings and several preferred embodiments. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention. For test methods in the following embodiments where specific conditions are not specified, the test methods in the embodiments are all performed under conventional conditions. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.
[0075] Example 1
[0076] A 50 mg / mL polyvinyl alcohol (PVA) solution was prepared. 5 mg / mL carbon nanotube slurry (CNT) and the 50 mg / mL PVA solution were mixed at a volume ratio of 1:5 and stirred. Cells were disrupted and dispersed evenly for 5 hours to form a CNT / PVA mixed solution. Polyanionic polystyrene sulfonic acid (PSSA) was added dropwise to the above mixed solution to form a PSSA concentration of 50 mg / mL. After adjusting the pH of the mixed solution to approximately 1, it was subjected to vacuum degassing. A crosslinking agent, glutaraldehyde solution, was added to the above mixed solution at a mass ratio of 1:100. The frozen polyanionic CNT / PVA hydrogel was obtained by liquid nitrogen cryogenic casting. After freezing, the composite gel was thawed at room temperature and then placed in pure water for 24 hours. The thawed sample was then frozen in a refrigerator and dried using a freeze dryer for 48 hours to obtain a polyanionic CNT / PVA composite aerogel. This aerogel was then soaked in water to obtain a polyanionic CNT / PVA hydrogel. Further studies were conducted, and the average orientation pore size was statistically analyzed. The performance at an optical power density of 1 kWm² was also investigated. -2 The simulated solar thermal evaporation rate was measured, and the test results are shown in Table 1.
[0077] Example 2
[0078] A 50 mg / mL polyvinyl alcohol (PVA) solution was prepared. 5 mg / mL carbon nanotube slurry (CNT) and the 50 mg / mL PVA solution were mixed at a volume ratio of 1:5 and stirred. Cells were disrupted and dispersed evenly for 5 hours to form a CNT / PVA mixed solution. Polycationic polyethyleneimine (PEI) was added dropwise to the above mixed solution to form a PEI concentration of 50 mg / mL. After adjusting the pH of the mixed solution to approximately 1, it was subjected to vacuum degassing. A crosslinking agent, glutaraldehyde solution, was added to the above mixed solution at a mass ratio of 1:100. The mixture was then cryogenically cast using liquid nitrogen to obtain a frozen polycationic CNT / PVA hydrogel. After freezing, the composite gel was thawed at room temperature and then placed in pure water for 24 hours. The thawed sample was then frozen in a refrigerator and dried using a freeze dryer for 48 hours to obtain a polycation-regulated CNT / PVA composite aerogel. This aerogel was then soaked in water to obtain a polycation-regulated CNT / PVA hydrogel. Further studies were conducted, and the average orientation pore size was statistically analyzed. The performance at an optical power density of 1 kW / m² was also investigated. -2 The simulated solar thermal evaporation rate was measured, and the test results are shown in Table 1.
[0079] Example 3
[0080] A 50 mg / mL polyvinyl alcohol (PVA) solution was prepared. 5 mg / mL carbon nanotube slurry (CNT) and 50 mg / mL PVA solution were mixed at a volume ratio of 1:5 and stirred until the cells were lysed and evenly dispersed for 5 hours, forming a CNT / PVA mixed solution. The poly(diallylammonium chloride-acrylamide-acrylic acid) (P(DMDAAC-AM-AA)) of the amphoteric electrolyte was added dropwise to the above mixed solution to form a PEI concentration of 50 mg / mL. After adjusting the pH of the mixed solution to approximately 1, it was subjected to vacuum degassing. A glutaraldehyde crosslinking agent solution was added to the above mixed solution at a mass ratio of 1:100. The mixture was then cryogenically cast using liquid nitrogen to obtain the frozen poly(amphoteric electrolyte) CNT / PVA hydrogel. After freezing, the composite gel was thawed at room temperature and then placed in pure water for 24 hours. The thawed sample was then frozen in a refrigerator and dried using a freeze dryer for 48 hours to obtain a CNT / PVA composite aerogel regulated by amphoteric electrolyte. This aerogel was then soaked in water to obtain a CNT / PVA hydrogel regulated by amphoteric electrolyte. Further studies were conducted, and the average orientation pore size was statistically analyzed. The performance at an optical power density of 1 kW / m² was also investigated. -2 The simulated solar thermal evaporation rate was measured, and the test results are shown in Table 1.
[0081] Comparative Example 1
[0082] A 50 mg / mL polyvinyl alcohol (PVA) solution was prepared. 5 mg / mL carbon nanotube slurry (CNT) and the 50 mg / mL PVA solution were mixed at a volume ratio of 1:5 and stirred. Cells were disrupted and dispersed evenly for 5 hours to form a CNT / PVA mixed solution. Polyanionic polystyrene sulfonic acid (PSSA) was added dropwise to the above mixed solution to form a PSSA concentration of 50 mg / mL. After adjusting the pH of the mixed solution to approximately 1, it was subjected to vacuum degassing. A crosslinking agent, glutaraldehyde solution, was added to the above mixed solution at a mass ratio of 1:100. The frozen polyanionic CNT / PVA hydrogel was obtained using conventional freeze casting. After freezing, the composite gel was thawed at room temperature and then placed in pure water for 24 hours. The thawed sample was then frozen in a refrigerator and dried using a freeze dryer for 48 hours to obtain a polyanionic CNT / PVA composite aerogel. This aerogel was then soaked in water to obtain a polyanionic CNT / PVA hydrogel. Further studies were conducted, and the average orientation pore size was statistically analyzed. The performance at an optical power density of 1 kWm² was also investigated. -2 The simulated solar thermal evaporation rate was measured, and the test results are shown in Table 1.
[0083] Comparative Example 2
[0084] A 50 mg / g / mL polyvinyl alcohol (PVA) solution was prepared. 5 mg / g / mL carbon nanotube slurry (CNT) and 50 mg / mL PVA solution were mixed at a volume ratio of 1:5 and stirred. Cells were disrupted for 5 hours to achieve uniform dispersion, forming a CNT / PVA mixed solution. No polyelectrolyte was added. After adjusting the pH of the mixed solution to approximately 1, it underwent vacuum degassing. A glutaraldehyde crosslinking agent solution was added to the mixed solution at a mass ratio of 1:100. CNT / PVA hydrogels were obtained by liquid nitrogen directional cryogenic casting. The frozen composite gels were thawed at room temperature, then placed in pure water and allowed to stand for 24 hours. After standing, the samples were frozen in a refrigerator and then freeze-dried for 48 hours to obtain CNT / PVA composite aerogels. These aerogels were then expanded in water to obtain CNT / PVA hydrogels. Further studies were conducted, and the average oriented pore size was statistically analyzed. The performance at a light power density of 1 kW / m² was also investigated. -2 The simulated solar thermal evaporation rate was measured, and the test results are shown in Table 1.
[0085] Table 1. Test results of photothermal temperature and photothermal evaporation rate of the nano-carbon hydrogels obtained in Examples 1-3 and Comparative Examples 1-2.
[0086]
[0087] Example 4
[0088] A 50 mg / mL polyvinyl alcohol (PVA) solution was prepared. 5 mg / mL graphene oxide (GO) slurry and 50 mg / mL PVA solution were mixed at a volume ratio of 1:5 and stirred. Cells were disrupted and dispersed evenly for 5 hours to form a GO / PVA mixed solution. Polyanionic polystyrene sulfonic acid (PSSA) was added dropwise to the above mixed solution to form a PSSA concentration of 50 mg / mL. After adjusting the pH of the mixed solution to approximately 1, it was subjected to vacuum degassing. A crosslinking agent, glutaraldehyde solution, was added to the above mixed solution at a mass ratio of 1:100. The frozen polyanionic GO / PVA hydrogel was obtained by liquid nitrogen cryogenic casting. After freezing, the composite gel was thawed at room temperature and then placed in pure water for 24 hours. The thawed sample was then frozen in a refrigerator and dried using a freeze dryer for 48 hours to obtain a polyanionic regulated GO / PVA composite aerogel. After soaking in water, a polyanionic GO / PVA hydrogel was obtained. Further studies were conducted, and the average orientation pore size was statistically analyzed. The performance at an optical power density of 1 kW / m² was also investigated. -2 The simulated water evaporation rate under sunlight was measured, and the test results are shown in Table 2.
[0089] Example 5
[0090] A 50 mg / mL polyvinyl alcohol (PVA) solution was prepared. 5 mg / mL carbon black slurry (CB) and the 50 mg / mL PVA solution were mixed at a volume ratio of 1:5 and stirred. Cells were disrupted and dispersed evenly for 5 hours to form a CB / PVA mixed solution. Polyanionic polystyrene sulfonic acid (PSSA) was added dropwise to the above mixed solution to form a PSSA concentration of 50 mg / mL. After adjusting the pH of the mixed solution to approximately 1, it was subjected to vacuum degassing. A crosslinking agent, glutaraldehyde solution, was added to the above mixed solution at a mass ratio of 1:100. The mixture was then cryogenically cast using liquid nitrogen to obtain the frozen polyanionic CB / PVA hydrogel. After freezing, the composite gel was thawed at room temperature and then placed in pure water for 24 hours. The thawed sample was then frozen in a refrigerator and dried using a freeze dryer for 48 hours to obtain a polyanionic regulated CB / PVA composite aerogel. After soaking in water, a polyanionic CB / PVA hydrogel was obtained. Further studies were conducted, and the average orientation pore size was statistically analyzed. The performance at an optical power density of 1 kW / m² was also investigated. -2 The simulated solar thermal evaporation rate was measured, and the test results are shown in Table 2.
[0091] Example 6
[0092] A 50 mg / mL polyethylene glycol (PEG) solution was prepared. 5 mg / mL carbon nanotube slurry (CNT) and 50 mg / mL PEG solution were mixed at a volume ratio of 1:5 and stirred. Cells were disrupted and dispersed evenly for 5 hours to form a CNT / PEG mixed solution. Polyanionic polystyrene sulfonic acid (PSSA) was added dropwise to the above mixed solution to form a PSSA concentration of 50 mg / mL. After adjusting the pH of the mixed solution to approximately 1, it was subjected to vacuum degassing. A crosslinking agent, glutaraldehyde solution, was added to the above mixed solution at a mass ratio of 1:100. The mixture was then cryogenically cast using liquid nitrogen to obtain the frozen polyanionic CNT / PEG hydrogel. After freezing, the composite gel was thawed at room temperature and then placed in pure water for 24 hours. The thawed sample was then frozen in a refrigerator and dried using a freeze dryer for 48 hours to obtain a polyanionic CNT / PEG composite aerogel. This aerogel was then soaked in water to obtain a polyanionic CNT / PEG hydrogel. Further studies were conducted, and the average orientation pore size was statistically analyzed. The performance at an optical power density of 1 kWm² was also investigated. -2 The simulated solar thermal evaporation rate was measured, and the test results are shown in Table 2.
[0093] Example 7
[0094] A 20 mg / mL polyethylene glycol (PEG) solution was prepared. 5 mg / mL carbon nanotube slurry (CNT) and the 20 mg / mL PEG solution were mixed at a volume ratio of 1:5 and stirred. Cells were disrupted and dispersed evenly for 5 hours to form a CNT / PEG mixed solution. Polyanionic polystyrene sulfonic acid (PSSA) was added dropwise to the above mixed solution to form a PSSA concentration of 20 mg / mL. After adjusting the pH of the mixed solution to approximately 1, it was subjected to vacuum degassing. A crosslinking agent, glutaraldehyde solution, was added to the above mixed solution at a mass ratio of 1:100. The frozen polyanionic CNT / PEG hydrogel was obtained by liquid nitrogen cryogenic casting. After freezing, the composite gel was thawed at room temperature and then placed in pure water for 24 hours. The thawed sample was then frozen in a refrigerator and dried using a freeze dryer for 48 hours to obtain a polyanionic CNT / PEG composite aerogel. This aerogel was then soaked in water to obtain a polyanionic CNT / PEG hydrogel. Further studies were conducted, and the average orientation pore size was statistically analyzed. The performance at an optical power density of 1 kWm² was also investigated. -2 The simulated solar thermal evaporation rate was measured, and the test results are shown in Table 2.
[0095] Table 2 shows the test results of photothermal temperature and photothermal evaporation rate of the nano-carbon hydrogels obtained in Examples 4-7.
[0096]
[0097] Furthermore, infrared thermal imaging was used to observe the photothermal conversion state of the aforementioned polyelectrolyte carbon-based hydrogel under a solar power density. Figure 3 This demonstrates that polyelectrolyte carbon-based hydrogels possess excellent photothermal conversion properties.
[0098] In addition, the inventors of this case also conducted experiments with other raw materials, process operations, and process conditions described in this specification, referring to the aforementioned embodiments, and obtained relatively ideal results in all cases.
[0099] All aspects, embodiments, features, and examples of this invention should be considered illustrative in all respects and are not intended to limit the invention. The scope of the invention is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.
[0100] Although the invention has been described with reference to illustrative embodiments, those skilled in the art will understand that various other changes, omissions, and / or additions can be made without departing from the spirit and scope of the invention, and that elements of the embodiments can be substituted with substantially equivalents. Furthermore, many modifications can be made without departing from the scope of the invention to adapt particular situations or materials to the teachings of the invention. Therefore, this invention is not intended to be limited to the specific embodiments disclosed for carrying out the invention, but rather is intended to encompass all embodiments falling within the scope of the appended claims. Moreover, unless specifically stated otherwise, any use of the terms first, second, etc., does not indicate any order or importance, but is used to distinguish one element from another.
Claims
1. A polyelectrolyte carbon-based hydrogel, characterized in that: The polyelectrolyte carbon-based hydrogel has an ordered oriented three-dimensional porous network structure formed by cross-linking of water-soluble gel, polyelectrolyte, and nano-carbon, and the ordered oriented three-dimensional porous network structure is a three-dimensional interpenetrating double network structure formed by non-covalent cross-linking of polymer gel network and nano-carbon. The water-soluble gel includes at least one of chitosan, sodium alginate, polyvinyl alcohol, and polyethylene glycol; the nano-carbon material includes at least one of graphene, carbon nanotubes, graphyne, fullerene, nano-carbon black, activated carbon, and graphite powder; and the polyelectrolyte includes at least one of polyanionic electrolyte, polycationic electrolyte, and polyzwitterionic electrolyte. The polyelectrolyte carbon-based hydrogel has an oriented pore size of 1~20 μm and a porosity of 80~90%. The polyelectrolyte carbon-based hydrogel has a specific porosity at 1 kW / m³. -2 At the given light power density, the water evaporation rate is 1.8–4.3 kg / m³. -2 h -1 ; The preparation method of the polyelectrolyte carbon-based hydrogel includes: The water-soluble gel, water, and nano-carbon material are mixed evenly to obtain the first mixed solution; The polyelectrolyte was mixed thoroughly with the first mixed solution to obtain a second mixed solution, and the pH value was adjusted. The second mixed solution and crosslinking agent were mixed and then subjected to directional freeze casting at -20 ~ -196 °C to obtain a frozen nano-carbon composite gel. The frozen nano-carbon composite gel was freeze-dried to obtain a polyelectrolyte carbon-based aerogel, which was then soaked in water to obtain a polyelectrolyte carbon-based hydrogel.
2. The polyelectrolyte carbon-based hydrogel according to claim 1, characterized in that: The orientation pore size of the polyelectrolyte carbon-based hydrogel is 1~10 μm.
3. The polyelectrolyte carbon-based hydrogel according to claim 1, characterized in that, include: The water-soluble gel is mixed with water to obtain a polymer solution, and then nano-carbon materials are added to obtain the first mixed solution.
4. The polyelectrolyte carbon-based hydrogel according to claim 3, characterized in that: The mass concentration of the water-soluble gel in the polymer solution is 10~50 mg / mL.
5. The polyelectrolyte carbon-based hydrogel according to claim 3, characterized in that: The mass concentration of the nano-carbon material in the first mixed solution is 0.1~2 mg / mL.
6. The polyelectrolyte carbon-based hydrogel according to claim 1, characterized in that, include: The polyelectrolyte is stirred and mixed evenly with the first mixed solution to obtain a second mixed solution. The pH value is adjusted to 1-2, stirred evenly, and then vacuum degassing is performed.
7. The polyelectrolyte carbon-based hydrogel according to claim 1, characterized in that: The polyanionic electrolyte includes at least one of polyacrylic acid, polymethacrylic acid, polystyrene sulfonic acid, and polyvinylphosphoric acid.
8. The polyelectrolyte carbon-based hydrogel according to claim 1, characterized in that: The polycationic electrolyte includes at least one of polyethyleneimine and polyethyleneamine.
9. The polyelectrolyte carbon-based hydrogel according to claim 1, characterized in that: The zwitterionic electrolyte includes at least one of natural nucleic acids, proteins, and polydimethyldiallylammonium chloride-acrylamide-acrylic acid.
10. The polyelectrolyte carbon-based hydrogel according to claim 6, characterized in that: The mass concentration of the polyelectrolyte in the second mixed solution is 10~50 mg / mL.
11. The polyelectrolyte carbon-based hydrogel according to claim 6, characterized in that: The acid used to adjust the pH includes at least one of hydrochloric acid, sulfuric acid, and phosphoric acid.
12. The polyelectrolyte carbon-based hydrogel according to claim 11, characterized in that: The concentration of the acid is 0.1~1 mol / L.
13. The polyelectrolyte carbon-based hydrogel according to claim 6, characterized in that: The vacuum degassing treatment time is 20~60 min, the vacuum degree of the vacuum degassing treatment is 1~20 Pa, and the temperature of the vacuum degassing treatment is 15~30 ℃.
14. The polyelectrolyte carbon-based hydrogel according to claim 1, characterized in that, include: The crosslinking agent is added dropwise to the second mixed solution, poured into a cryogenic casting mold, and cryogenic nano-carbon composite gel is obtained by directional cryogenic casting.
15. The polyelectrolyte carbon-based hydrogel according to claim 14, characterized in that: The mass ratio of the crosslinking agent to the second mixed solution is 1:100 to 1:
200.
16. The polyelectrolyte carbon-based hydrogel according to claim 14, characterized in that: The crosslinking agent includes glutaraldehyde.
17. The polyelectrolyte carbon-based hydrogel according to claim 14, characterized in that: The directional cryogenic casting includes unidirectional or bidirectional cryogenic casting.
18. The polyelectrolyte carbon-based hydrogel according to claim 14, characterized in that: The working environment for directional cryogenic casting is a low-temperature constant-temperature reaction bath or liquid nitrogen.
19. The polyelectrolyte carbon-based hydrogel according to claim 14, characterized in that: The raw materials for the cryogenic casting mold include at least one of stainless steel, copper, aluminum, silicone, polytetrafluoroethylene, nylon, and plexiglass.
20. The polyelectrolyte carbon-based hydrogel according to claim 1, characterized in that, include: The frozen nano-carbon composite gel was thawed at room temperature and allowed to stand, then freeze-dried to obtain a polyelectrolyte carbon-based aerogel, which was then soaked in water to obtain a polyelectrolyte carbon-based hydrogel.
21. The polyelectrolyte carbon-based hydrogel according to claim 20, characterized in that: The settling time is 1 to 3 hours.
22. The polyelectrolyte carbon-based hydrogel according to claim 20, characterized in that: The freeze-drying time is 24-72 h, and the freeze-drying temperature is 10-30 ℃.
23. The polyelectrolyte carbon-based hydrogel according to claim 20, characterized in that: The vacuum degree of the freeze-drying process is 1~10 Pa.
24. The polyelectrolyte carbon-based hydrogel according to claim 20, characterized in that: The soaking time is 1 to 10 hours.
25. A polyelectrolyte carbon-based dry gel prepared by drying the polyelectrolyte carbon-based hydrogel according to any one of claims 1-24.
26. The application of the polyelectrolyte carbon-based hydrogel according to any one of claims 1-24 or the polyelectrolyte carbon-based dry gel according to claim 25 in the field of photothermal evaporation purification.
27. The application according to claim 26, characterized in that: The applications include those in seawater desalination, wastewater treatment, or heavy metal salt treatment.
Citation Information
Patent Citations
Efficient photo-thermal water evaporation carbon nanotube hydrogel as well as preparation method and application thereof
CN112934129A
Preparation method and application of hydrogel film with porous structure
CN118047973A
Hydrogel for solar water treatment as well as preparation method and application of hydrogel
CN117089088A